Divergent patterns of cognitive deficits and structural brain alterations between older adults in mixed-sex and same-sex relationships - Manca, Riccardo; Correro, Anthony N.; Gauthreaux, Kathryn; Flatt, Jason D. (Frontiers in Human Neuroscience, 2022)
Background: Sexual minority (SM) older adults experience mental health disparities. Psychiatric disorders and neuropsychiatric symptoms (NPS) are risk factors for cognitive decline. Although older people in same-sex (SSR) compared to mixed-sex relationships (MSR) perform more poorly on cognitive screening tests, prior studies found no differences in diagnosis rates of dementia or neuropsychological profiles. We sought to explore the role of NPS on neurocognitive outcomes for SM populations. We compared cognitive performance and structural brain parameters of older adults in SSR and MSR. Methods: Data were originally collected at Alzheimer’s Disease Research Centers (ADRCs). Inclusion criteria were: age of 55+ years, a study partner identified as a spouse/partner, and availability of T1-MRI brain volumes/thickness. Participants were labeled as either SSR or MSR based on their/their co-participant’s reported sex. We identified 1073 participants (1037 MSR - 555 cognitively unimpaired [CU]; 36 SSR - 23 CU) with structural MRI data, Mini-Mental State Exam (MMSE), and Neuropsychiatric Inventory Questionnaire (NPI-Q) scores. A subset of the overall sample completed comprehensive neuropsychological assessment (n = 939; 908 MSR - 494 CU; 31 SSR – 22 CU). Covariates included in statistical models were age, sex, education, total intracranial volume, and apolipoprotein-E genotype. Results: Multivariate general linear models showed significant diagnosis-by-relationship interaction effect on the left parahippocampal gyrus volume. After stratification by relationship group, only cognitively impaired (CI) MSR had significantly smaller left parahippocampal volumes than MSR-CU. The SSR group showed better episodic memory performance. Severity of neuropsychiatric symptoms was negatively associated with volume/thickness of bilateral fronto-temporal areas and with MMSE scores, in the MSR group only. Conclusion: In our study, MSR participants presented with more a compromised cognitive profile than SSR participants. MSR-CI participants showed significantly smaller left medio-temporal volumes, a neural signature of AD. Neuropsychiatric symptoms predicted smaller fronto-temporal volumes in the MSR more extensively than in the SSR group. These findings may be due to unexplored protective factors against cognitive decline in SM elders. Indeed, social support has been proposed as a protective factor warranting future investigation.